2005
DOI: 10.1590/s1519-38292005000300003
|View full text |Cite
|
Sign up to set email alerts
|

Papel da vitamina A na prevenção do estresse oxidativo em recém-nascidos

Abstract: Vitamin A is recognized as an essential trace element in phases of intense growth and development such as pregnancy and childhood. The influence of this trace element is recognized in different metabolic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
5
0
3
Order By: Relevance
“…However, it is non that chlorophylls are unstable pigments and they can be better preserved by HTST (High Temperature Short Time) treatment; moreover, their effectiveness is improved with the intake of fresh food. Carotenoids can be used as food or food additive since they can reduce atherosclerosis progression and enhance immune response preventing the formation of free radicals and reactive oxygen species that can damage mitochondrial enzymes, plasma membrane, and DNA [39][40][41][42].…”
Section: Pigments (Chlorophyll and Carotenoids)mentioning
confidence: 99%
“…However, it is non that chlorophylls are unstable pigments and they can be better preserved by HTST (High Temperature Short Time) treatment; moreover, their effectiveness is improved with the intake of fresh food. Carotenoids can be used as food or food additive since they can reduce atherosclerosis progression and enhance immune response preventing the formation of free radicals and reactive oxygen species that can damage mitochondrial enzymes, plasma membrane, and DNA [39][40][41][42].…”
Section: Pigments (Chlorophyll and Carotenoids)mentioning
confidence: 99%
“…16 A vitamina A é um importante composto antioxidante, estando relacionada à redução do estresse oxidativo e de doenças crônicas degenerativas. 17 Além disso, possui funções importantes no crescimento e na diferenciação celular, e tem apresentado ação preventiva no desenvolvimento de alguns tumores, como de bexiga, mama, estômago e pele, em estudos desenvolvidos com animais. Pesquisas demonstram que o consumo regular de alimentos ricos em vitaminas A e C pode reduzir a incidência de câncer retal e de cólon.…”
Section: Discussionunclassified
“…However, this can be prevented if certain measures are taken. There is clear concern to establish a preventive measure to mitigate or combat the organic changes promoted by the oxidative stress in aging (Aranha et al, 2000, Cotran et al, 2000bFarinatti, 2002;Koury and Donangelo, 2003;Zoppi et al, 2003;Kehl and Cassini, 2004;Burneiko et al, 2005;Diniz et al, 2005a;Faine et al, 2005;Galhardi et al, 2005;Gomes et al, 2005;Novelli Filho and Novelli, 2005;Souza Jr et al, 2005). Cotran et al (2000b) andFarinatti (2002) propose that a lower caloric intake tends to absorb the cell damage process during the aging because such measures like reduced calories would promote the reduction of lipid peroxidation, lowest accumulation of oxidized protein and reduce the oxidative damage of DNA, which extended the maximum term of mammalians life.…”
Section: Antioxidants and Preventionmentioning
confidence: 99%
“…Diniz et al (2005b) found that fiber had also an antioxidant effect. Gomes et al (2005) considered vitamins C and E and carotenoids as exogenous antioxidants, since they were captivators of free radicals and some products of metabolism such as bilirubin and uric acid. According to Aranha et al (2000), vitamin C acts sweeping free radicals and nourishing the cells, and, therefore, essential to human metabolism.…”
Section: Antioxidants and Preventionmentioning
confidence: 99%